Educating, Protective, Healthy. A City Made of Belonging. - Carvalho, Maria do Carmo Brant de (2006)
Keeping in mind that a healthy, educating and protective city is a dream, this paper reflects on the idea of a Protective City, with the understanding that social protection, in its densest meaning, regards guarantees of security: quality of life, belonging and social inclusion. That is why the text includes other Educating City and Healthy City concepts. The phrase "healthy, educating, protective city" translates values that indicate collective living principals and direction in the city. The need to find a protective city for all, capable of articulating public policies for distribution of wealth is underscored. The soul of the city is expressed by values that orient distribution and the enjoyment of collective wealth. Therefore, it is necessary to reflect on the values that express the collective consciousness of its inhabitants; in other words, discussing the values that drive everyone's efforts in daily production in the city. Finally, it reinforces that there is a constant demand for building and disclosure of directions for public action: looking for truth, the good, the beautiful, the moral and the ethical. What is least in demand today are actions anchored in the false ethics of impartiality and neutrality.